Transformasi Digital Perikanan Berbasis Artificial Intelligence Untuk Mendukung Pengelolaan Sumber Daya Ikan Berkelanjutan - Maestro Laia; Destriman Laoli; Ratna Dewi Zebua; Okniel Zebua (Jurnal Perikanan dan Kelautan, 2026)
Digital transformation has become one of the key strategies for supporting sustainable fisheries resource management. This study aims to examine the role of Artificial Intelligence (AI) in improving efficiency, productivity, and effectiveness within the fisheries sector. The research employed a literature review approach by analyzing scientific publications, international organization reports, and related documents on AI applications in capture fisheries, aquaculture, and fisheries supply chains. The findings indicate that AI can enhance the accuracy of fish stock prediction, support the detection of Illegal, Unreported, and Unregulated (IUU) fishing activities, optimize aquaculture systems through automated feeding and disease detection, and improve the efficiency of fisheries product distribution. However, the implementation of AI still faces challenges, including limited digital infrastructure, high investment costs, and insufficient human resource capacity. Overall, AI has significant potential to become an innovative solution for developing a modern, efficient, and sustainable fisheries sector.